2015
DOI: 10.7863/ultra.15.02038
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Quantification of Pronator Quadratus Activity During Gripping Effort

Abstract: The data revealed that the superficial head of the pronator quadratus more actively contracts when the forearm is in pronation, whereas the deep head constantly contracts at all positions. This study suggests that both heads of the pronator quadratus also play a role in grip strength, but the superficial head contributes more to pronation strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Further studies have also identified the strong correlation with grip strength and pronation strength advocated for the need of normative values of pronation torque and grip strength in order to improve the quality of the clinical assessment of an injured wrist [ 18 ]. Testing these in our study identified similar traits as both outcomes were highly correlated with one another [ 19 ].…”
Section: Discussionmentioning
confidence: 90%
“…Further studies have also identified the strong correlation with grip strength and pronation strength advocated for the need of normative values of pronation torque and grip strength in order to improve the quality of the clinical assessment of an injured wrist [ 18 ]. Testing these in our study identified similar traits as both outcomes were highly correlated with one another [ 19 ].…”
Section: Discussionmentioning
confidence: 90%
“…They emphasized the importance of this muscle and postulated that deep head stabilizes the distal radioulnar joint and the superficial head initiates pronation. In addition to these functions, the PQ muscle is the key point indicator in the diagnosis of occult distal forearm fractures on plain radiographs [4,16]. However, sensitivity and specificity of the pronator sign has been questioned in the literature regarding the diagnosis of occult distal forearm fractures on plain radiographs [5,6,8,18].…”
Section: Discussionmentioning
confidence: 99%
“…While the superficial layer of PQ acts in coordination with the pronator teres and serves for forearm pronation, deep layer inserts joint capsule and take part in radio-ulnar joint stabilization [1][2][3]. In addition, both heads of the pronator quadratus also play a role in grip strength [4]. The obliteration of the fat plane between the pronator quadratus and the flexor digitorum profundus muscles which is a radiolucent plane that can be detected on lateral radiographs of the distal forearm namely the pronator sign has been reported since 1960s as an important diagnostic tool for the detection of the occult distal radius and ulna traumatic fractures [5].…”
Section: Introductionmentioning
confidence: 99%